ASSISTANCE OFFERED TO PREGNANT WOMEN AT THE HEALTH UNIT OF RIBEIRÃO PRETO: THE PRACTICE OF EVENTUAL AND CURATIVE ACTIONS PRACTICE - Maria das Dores do Vale Oba; Maria Solange Guarino Tavares (Universidade Federal do Paraná, 1998)
This study was undergone at two District Health Units, which give assistance to pregnant women in the municipality of Ribeirão Preto-SP. The objective of this paper was to know and identify the profile of the assistance given to women who use these services. One can observe that the reorganization of the health services in Ribeirão Preto strengthen the medicai assistance as an hegemonic practice, with the individual survey about the complaints and/or health problems. One can notice that when in contact with medicai knowledge, the clients question very little, leading to a very brief medicai appointment and with no bond, related to physical examination, tocoginecologic and complementary exams, with no space for the women's speech and questions.